The Role of Critical Thinking in The Preparation of High-Level Indonesian Questions by Pre-Service Teachers - Sri Wahyuni; Frida Siswiyanti; Itznaniyah Umie Murniatie; Prayitno Tri Laksano; Lilik Wahyuni; Ifit Novita Sari (Balai Bahasa Provinsi Bali, 2025)
This study aims to (1) describe the role of pre-service teachers’ critical thinking skills in their ability to formulate higher-order Indonesian language questions, and (2) identify which aspects of critical thinking have the most significant influence on this ability. A quantitative correlational approach was employed, with data collected from 71 pre-service teachers through a critical thinking skills test and an analysis of the higher-order questions they created. The data were analyzed using correlation tests, one-way ANOVA, and Post Hoc LSD analysis to examine relationships and differences in performance based on levels of critical thinking. The findings show a significant positive relationship between critical thinking and the ability to design analytical, evaluative, and creative questions. Pre-service teachers with higher levels of critical thinking demonstrated better performance in constructing cognitively complex questions. The ANOVA results (F = 55.632; p < 0.05) confirmed significant differences among the low-, medium-, and high-critical-thinking groups. These findings affirm that critical thinking is a key foundation for developing higher-order questioning skills. Therefore, teacher education programs should integrate inquiry-based learning, metacognitive reflection, and technology-based supports such as AI-assisted scaffolding to strengthen pre-service teachers’ critical and reflective thinking abilities. AbstrakPenelitian ini bertujuan untuk (1) mendeskripsikan peran keterampilan berpikir kritis guru prajabatan dalam kemampuan mereka menyusun pertanyaan Bahasa Indonesia tingkat tinggi, serta (2) mengidentifikasi aspek berpikir kritis yang paling berpengaruh terhadap kemampuan tersebut. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Data dikumpulkan dari 71 guru prajabatan melalui tes berpikir kritis dan analisis terhadap pertanyaan tingkat tinggi yang mereka buat. Data dianalisis menggunakan uji korelasi, ANOVA satu arah, dan uji Post Hoc LSD untuk melihat hubungan dan perbedaan kemampuan berdasarkan tingkat berpikir kritis. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara keterampilan berpikir kritis dan kemampuan menyusun pertanyaan analitis, evaluatif, serta kreatif. Guru prajabatan dengan kemampuan berpikir kritis tinggi menunjukkan hasil yang lebih baik dalam menyusun pertanyaan kompleks secara kognitif. Hasil ANOVA (F = 55,632; p < 0,05) juga menegaskan adanya perbedaan yang bermakna antara kelompok berpikir kritis rendah, sedang, dan tinggi. Temuan ini menegaskan bahwa berpikir kritis merupakan dasar penting dalam mengembangkan kemampuan bertanya tingkat tinggi. Oleh karena itu, program pendidikan guru perlu mengintegrasikan pembelajaran berbasis inkuiri, refleksi metakognitif, serta dukungan teknologi seperti AI-assisted scaffolding untuk memperkuat kemampuan berpikir kritis dan reflektif calon guru.